Effects of corn source and fat level on growth performance of grow-finish pigs reared in a commercial facility - Hastad, C.W.; Jones, C.L.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,144 gilts (initially 110.4 lb, PIC) was used in a commercial research facility to evaluate the effects of corn source (NutriDense™, BASF, or #2 Yellow Dent) and added fat (averaging 0, 3, and 6%) on pig performance and carcass traits. Energy levels were based such that the higher energy (assuming 5% greater ME than #2 yellow dent) in NutriDense corn (with or without added fat) was calculated to be equal to that provided by yellow dent corn and added fat. In each phase, the first treatment diet contained yellow dent corn and no added fat. In the next dietary treatment, yellow dent corn was replaced with NutriDense corn, and then fat was added (2.7 to 3.2% based on phase) to the yellow dent corn-based diet to equal the energy content of the NutriDense corn diet. This amount of added fat was then added to the NutriDensebased diet. The last yellow dent corn based diet used 5.2 to 6.2% (based on phase) added fat to equal the energy content of the second NutriDense corn diet. This amount of fat was then added to the NutriDense-base diet to complete the treatment structure. For the overall study, pigs fed NutriDense corn had greater (P<0.04) ADG compared to pigs fed yellow dent corn. There was a corn source by fat level interaction (P<0.01) observed for ADFI and F/G. When fat was added to diets containing NutriDense corn, F/G decreased linearly, whereas when fat was added to yellow dent corn the greatest improvement in feed efficiency was observed with the first 3% added fat. Adding fat to diets also increased (P<0.01) final and carcass weight, and tended (P<0.09) to increase backfat thickness. Using the known energy values of yellow dent corn and fat, we calculated NutriDense corn to have 5.3% more ME than yellow dent corn. These results are similar to previous research in nursery pigs at Kansas State University showing 5% more ME for NutriDense corn than yellow dent corn. This also supports work done the University of Illinois which determined that NutriDense corn has 6.5% more ME than yellow dent corn. Increasing the dietary energy level above a yellow dent corn-soybean meal-based diet with 6% added fat improved ADG and F/G in grow-finish pigs. Furthermore, pigs fed NutriDense corn had greater ADG than pigs fed yellow dent corn.
Keywords: Corn; Fat; Energy; Grow-Finish pigs; Swine